The effect of feedback times in learning block and stroke skills of volleyball - صباح حسين عائد (Journal of Physical Education, 2019)
This thesis included five chapter : The Problem of the study included the difficulty for pupils in learning same of the skills of volley ball and research opinion study of using tow type of feedback , And the Aims of study to know effect of feedback times in learning tow skills of volleyball , And using in study Experimental Research of design (three group) – tow experimental groups and one controlling group , and selected subjects from pupils of Al-buhtery school , and test the subjects and than teaching by learning program and than test after , after that display of results of research and conclusions and recommendation that is better to learning block and stroke of volleyball by using feedback specification the end feedback